BAC-FISH refutes report of an 8p22-8p23.1 inversion or duplication in 8 patients with Kabuki syndrome - Hobart Holly H; Morris Colleen A; Kimberley Kendra W (BMC, 2006)
Abstract Background Kabuki syndrome is a multiple congenital anomaly/mental retardation syndrome. The syndrome is characterized by varying degrees of mental retardation, postnatal growth retardation, distinct facial characteristics resembling the Kabuki actor's make-up, cleft or high-arched palate, brachydactyly, scoliosis, and persistence of finger pads. The multiple organ involvement suggests that this is a contiguous gene syndrome but no chromosomal anomalies have been isolated as an etiology. Recent studies have focused on possible duplications in the 8p22-8p23.1 region but no consensus has been reached. Methods We used bacterial artificial chromosome-fluorescent in-situ hybridization (BAC-FISH) and G-band analysis to study eight patients with Kabuki syndrome. Results Metaphase analysis revealed no deletions or duplications with any of the BAC probes. Interphase studies of the Kabuki patients yielded no evidence of inversions when using three-color FISH across the region. These results agree with other research groups' findings but disagree with the findings of Milunsky and Huang. Conclusion It seems likely that Kabuki syndrome is not a contiguous gene syndrome of the 8p region studied.